Project management planning and scheduling techniques - Bansal, Vijay Kr
"A highly readable guide to the essentials of project planning, scheduling, and control. This book explains the theory behind the methods and makes effective use of learning outcomes, exercises, diagrams and examples to develop clear and actionable knowledge for students and project managers. The book can be used as a classroom textbook or self-study guide for project managers taking their professional qualifications and includes examples from a wide range of project management scenarios. It is suitable for planning and scheduling courses in the fields of industrial, civil and mechanical engineering, construction and management"